1986
DOI: 10.1093/ajcn/43.1.68
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cysteine-containing peptides released during meat digestion on iron absorption in humans

Abstract: In order to investigate the constituents responsible for the enhancing effect of meat on intestinal iron absorption in humans, two different types of peptic digestion extracts were prepared from 100 g of beef, in which the thiol groups of the resulting peptides were either oxidized (CYS-), or left untreated (CYS+). The absorption of radioiron mixed with 250 g of maize was more than twofold greater when consumed along with the CYS+ extract than with the CYS- (p less than 0.05). It is suggested that the enhancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(67 citation statements)
references
References 20 publications
0
67
0
Order By: Relevance
“…The absorption of non-haem iron is influenced by both enhancing and inhibitory factors in the diets. Ascorbic acid from fruits and vegetables and meat/fish/poultry are the main enhancing substances for iron absorption (Taylor et al, 1986;Ballot et al, 1987). Phytic acid from cereal grains and legumes (Hallberg et al, 1987;Hurrell et al, 1992), and polyphenol compounds from tea and coffee (Hurrell et al, 1999) are the major inhibitory substances.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption of non-haem iron is influenced by both enhancing and inhibitory factors in the diets. Ascorbic acid from fruits and vegetables and meat/fish/poultry are the main enhancing substances for iron absorption (Taylor et al, 1986;Ballot et al, 1987). Phytic acid from cereal grains and legumes (Hallberg et al, 1987;Hurrell et al, 1992), and polyphenol compounds from tea and coffee (Hurrell et al, 1999) are the major inhibitory substances.…”
Section: Discussionmentioning
confidence: 99%
“…They can be conveniently divided into four groups: (i) those that are freely water soluble; (ii) those that are poorly water soluble but soluble in dilute acids such as gastric juice; (iii) those that are water insoluble but poorly soluble in dilute acid; and (iv) protected iron compounds. The table gives guideline values for relative bioavailability in rat and man and a relative cost factor (Bothwell et al, 1992;Hurrell, 1985;Taylor et al, 1986). The bioavailability of iron for intake is depending upon the solubility in water.…”
Section: Iron Fortificantsmentioning
confidence: 99%
“…Compounds poorly soluble in dilute acids include ferric pyrophosphate, ferric orthophosphate, and ferric ammonium orthophosphate (Taylor et al, 1986;Patrick, 1985). They are the most often-used compounds in food fortification and their main advantage is that they cause no organoleptic problems.…”
Section: Compounds Poorly Soluble In Dilute Acidsmentioning
confidence: 99%
“…The ability of amino acids to enhance iron absorption is not yet clear. Some studies have reported that certain amino acids increased lron absorption (Van Campen, 1973;Martinez-Torres et a/., 1981;Taylor et al, 1986); whereas, the study of Layrisse et al ( 1984) has shown no effect. Previous studies have shown that the animal tissues (meat) and peptides enhance iron absorption and iron uptake (Slatkavitz & Clydesdale, 1988;Gordon & Godber, 1989;Kapsokefalou & Miller, 199 l;Garcia et al, 1996;Glahn et a/ , 1 996).…”
mentioning
confidence: 98%